Characteristics of Japanese Garden - Jonuzakov Abduvali Esirgapovich; Djuraeva Gulchehra Nuruldlaevna; Gaibullaeva Muattar Olimjonovna (International Journal on Integrated Education, 2022)
The article briefly discusses the emergence of garden art in Japan, its main types and analyzes the main features of the Japanese garden.